The state of the duodenal villi in rats under epichlorohydrin and drugs influence - A. S. Smirnov; M. A. Mirzebasov; S. M. Smirnov (Zaporožskij Medicinskij Žurnal)
Introduction. The modern environment is polluted by xenobiotics which can cause the development of pathological processes. One of xenobiotics is epichlorohydrin (ECH). The impact of this xenobiotic causes changes in the state of various organs, including the organs of the digestive system. However, the effects of ECH on the duodenum have not been investigated.